IMPACT OF INDEPENDENT LEARNING POLICY AND COMPENSATION ON TEACHER PERFORMANCE THROUGH JOB SATISFACTION AS A MEDIATING VARIABLE - Sumardiyanto, Sumardiyanto; Dassucik, Dassucik; Rasyidi, Ahmad Hafas (Consilium: Education and Counseling Journal, 2025)
This study explores the influence of the Independent Learning Policy and compensation on teacher performance, with job satisfaction as a mediating variable. Using a quantitative research design and Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, data were collected from 107 teachers across three junior high schools in Situbondo Regency. The results indicate that the Independent Learning Policy significantly impacts teacher performance both directly and indirectly through job satisfaction, with a path coefficient of 0.347 (p = 0.005). Compensation also plays a key role, directly influencing job satisfaction (path coefficient = 0.270, p < 0.001) and indirectly affecting teacher performance through job satisfaction (path coefficient = 0.130, p = 0.008). The adjusted RÂ² values reveal that 89.8% of the variance in job satisfaction and 86.4% of the variance in teacher performance are explained by the model. These findings highlight the interconnected roles of educational policies, compensation, and job satisfaction in enhancing teacher performance, providing actionable insights for policymakers and school administrators to foster supportive environments that promote educational excellence.